Quantifying the effectiveness of ITS in improving safety of VRUs. Issue 3 (24th March 2017) - Silla, Anne; Rämä, Pirkko; Leden, Lars; van Noort, Martijn; de Kruijff, Janiek; Bell, Daniel; Morris, Andrew; Hancox, Graham; Scholliers, Johan
Abstract : This paper presents the results of a safety impact assessment, providing quantitative estimates of the safety impacts of ten intelligent transport systems (ITS) which were designed to improve safety, mobility and comfort of vulnerable road users (VRUs). The evaluation method originally developed to assess safety impacts of ITS for cars was now adapted for assessing safety impacts of ITS for VRUs. The main results of the assessment showed that nine ITS included in the quantitative safety impact assessment affected traffic safety in a positive way by preventing fatalities and injuries. At full penetration the highest effects were obtained for Pedestrian and Cyclists Detection System + Emergency Braking (PCDS+EBR), VRU Beacon System (VBS) and Intersection Safety (INS). The estimates for PCDS+EBR showed the maximum reduction of 7.5% on all road fatalities at full penetration, which comes down to an medium estimate of around 1, 900 fatalities saved per year in the EU‐28 when applying the 2012 accident data and 100% penetration rate. The results regarding future scenarios showed the highest effects in number of reduced fatalities per system in the European Union (EU)‐28 in 2030 for PCDS+EBR (−200 fatalities), Blind Spot Detection (BSD) (−22 fatalities), INS (−20 fatalities) and VBS (−11 fatalities).